Attitudinal Analysis of Kompas Online & Republika Concerning The Relocation of Indonesia's Capital City News - Faizal Risdianto; Sumarlam Sumarlam; Tri Wiratno; Djatmika Djatmika (Universitas Sebelas Maret, 2022)
This study aims to describe the language used by Kompas Online and Republika regarding the relocation of the Indonesian capital city. This study focuses on the identification includes three aspects of the attitudinal lexis of the appraisal system: affect, judgment, and appreciation. The data collection was in form of online texts made by reporters. The qualitative descriptive method was used in this study. The instrument of this research is observation. The collected data were analyzed using the theories of Martin & Rose and Miles & Huberman. The research showed that the number of positive attitude lexis was more than the negative attitude lexis. Among 150 Data, 59.3% (89 data out of a total of 150 Data) were positive, and 40.7% were negative (61 data out of 150 data). If the data is calculated in detail, the percentage of the affect was 38% Affect, 8% Judgment, and 54% appreciation. The low difference in the number of positive and negative assessment data indicates that there are crucial and controversial problems faced by the Government, community leaders, and the general public regarding the idea of the relocation of Indonesia's capital city.